The Model for Improving Foreign Language Skills of Islamic Boarding School Students at the Muhammadiyah Imam Syuhodo Modern Islamic Boarding School - Miftakhul Miftakhul; mutohharun.jinan@ums.ac.id (Lembaga Pendidikan Islam Ma'aarif NU Kabupaten Magetan, 2024)
ABSTRACT In studying and developing languages in Islamic boarding schools, of course a platform is needed that makes it easier for students to understand and learn foreign languages in Islamic boarding schools. The IPM organization is a forum that can hone and support the language skills of students in Islamic boarding schools. Within the IPM organization there is a language division that can help students' language skills. It is hoped that students can master Indonesian, Arabic and English with the existence of a language division at the Islamic boarding school. This research aims to determine the work program implemented by the Muhammadiyah Student Association organization as well as supporting and inhibiting factors in improving the foreign language skills of female students at the Imam Syuhodo modern Muhammadiyah Islamic boarding school. This research uses a descriptive qualitative approach with the type of field research. Data collection methods are observation, interviews and documentation. Next, the data was tested for validity using triangulation techniques, and then analyzed descriptively. The results of this research show the work program implemented by IPM in improving female students' foreign language skills, namely: language day, mufrodat or vocabulary, ta'bir or insya, imla' or dictation, muhadatsah or conversation, musyahadah or listening, language carnival, qoriyatul lughoh, and muhadhoroh. The supporting factors for implementing the work program in improving female students' language skills are: The quality of the dormitory ustadzah, the quality of the Ustadzah supervisors and administrators of the IPM language division, a supportive dormitory environment. Meanwhile, the inhibiting factors are: Alignment of the IPM language division administrators in carrying out work programs, lack of awareness among female students.